Development of a Protocol for PCR Based Rapid Identification of White Spot Syndrome Virus in Tiger Shrimp, Penaeus monodon Fab. - Islam, MN; Ail, MR; Tareque, AMHB; Khatun, MM; Ahsan, MN (Bangladesh Journal of Genetics and Biotechnology, 2009)
Key words: Penaeus; White spot syndrome (WSSV); virus; tiger shrimp; PCR Bangladesh j. genet. biotechnol. 7(1&2): 37-42 2006 (June & December)